Bayasibulala: #AmINext? an analysis of Instagram as a tool for activism against Sexual Gender-Based Violence in South Africa - Mazana, Nandipha Nwabisa (Centre for Film and Media Studies, 2023)
Research over the years has shown that there is a global rise in hashtag activism, this type of activism has also inspired what scholars call - hashtag feminism. Hashtag feminism utilizes Social Networking Sites to raise awareness about issues that are often not covered in traditional news media outlets such as TV, newspapers, and Radio Stations. Through this paper, I seek to investigate how Instagram has become one of the Social Networking Sites that has recently started being used for online activism in South Africa. This is done by conducting a qualitative analysis of 700 posts from the hashtag #AmINext, with a period focus of 3 months during South Africa's COVID-19 Level-5 Lockdown. The findings suggest that activists follow similar lines of the hashtag and social media activism parameters such as those of the #MeToo and #BeenRapedNeverReported movements. The analysis found that activists use Instagram to participate in Citizen Journalism by sharing information, raising awareness, organizing, mobilizing, and advocating (Vegh, 2003). Furthermore, there is clear Civic Engagement and Citizen Journalism through things such as sharing information and having calls to action while utilizing hashtags as a way to gain momentum and attention. The findings suggest that these hashtags are able to cultivate a community of activists all around the country while also making sure to encourage more participation. The analysis also shows how there is an importance of such activism when movement is restricted due to national Lockdowns implemented to curb COVID-19, as many victims of SGBV found themselves at home and trapped with their abusers. In paying attention to this analysis, I conclude that perhaps through the exploration of new ways of activism, we can ensure that no voice is ever left behind. Furthermore, despite the possibilities of these new ways of raising awareness and activism, it is always important to see how we can apply the old with the new.